PEMETAAN KAWASAN TAMBANG BATUAN DI KABUPATEN SARMI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Agus Iksan; Harmonis Rante; Herbert Innah (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2024)
The aim of this research is to identify and analyze rock mining areas in Sarmi Regency using GIS and identifying the types of open pit mines that can be used at these rock mining locations. The benefits of preparing this research are providing contributions to related agencies, providing information on rock mining areas, creating maps of rock mining areas using GIS, apart from that being able to design rock mining systems, as well as increasing insight for researchers and readers regarding mapping rock mining areas using the SiG application. The steps taken are to carry out observations or surveys of rock mining locations, conduct interviews with miners and residents around the mining area and document activities in the field. After the data is obtained, the data is then analyzed using descriptive analysis techniques. The tools used are GPS, drones and digital cameras. The variables used are a questionnaire and spatial type in the form of maps and attribute data containing data on rock mining locations in Sarmi Regency.